Assessment and Intelligence of The Mathematical-Logical in Learning Computer Programming - Komang Setemen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
The research objective was to determine the influence of assessment types and mathematical-logical intelligence on computer programming learning outcomes after controlling numerical aptitude. Data were analyzed by analysis of covariance (ANCOVA) two lanes with one covariate. Results showed that 1) the results of learning computer programming students who attended the learning process with the assessment portfolio was higher than students who attended the learning process with the assessment project, 2) on a group of students who had high the intelligence mathematical-logical, the result of learning computer programming was most suitable to follow the process with portfolio, and 3) on a group of students who had a low mathematical-logical intelligence, computer programming learning outcomes was most suitable to follow the process with the assessment. Research to use the type of portfolio assessment in the learning process in order to improve student results.